(untitled) (Impetus, 2021)
This article presents some constructions and reflections carried out in the Pedagogy and Methodology project of Recreation in School, which arises in the Bachelor’s Degree in Recreation and Tourism of the National Pedagogical University. This writing promptly sets out its arguments to think about the pedagogy of recreation at school, thus as the tensions and arguments that can occur with relation to the emergence of new school knowledge.